H3 Relaxin Alleviates Migration, Apoptosis and Pyroptosis Through P2X7R-Mediated Nucleotide Binding Oligomerization Domain-Like Receptor Protein 3 Inflammasome Activation in Retinopathy Induced by Hyperglycemia - Yang, Kelaier; Liu, Jiannan; Zhang, Xiaohui; Ren, Ziqi; Gao, Lei; Wang, Ying; Lin, Wenjian; Ma, Xuefei; Hao, Ming; Kuang, Hongyu (Frontiers in Pharmacology, 2020)
Introduction: P2X7R excitation-interrelated NLRP3 inflammasome activation induced by high glucose contributes to the pathogenesis of diabetic retinopathy (DR). Relaxin-3 is a bioactive peptide with a structure similar to insulin, which has been reported to be effective in diabetic cardiomyopathy models in vivo and in vitro. However, it is not known whether relaxin-3 has a beneficial impact on DR, and the underlying mechanisms of the effect are also remain unknown. Methods and Results: The retinas of male streptozotocin (STZ)-induced diabetic Sprague-Dawley (SD) rats were characterized. Human retinal microvascular endothelial cells (HRMECs) were used to evaluate the anti-inflammatory, antiapoptotic, antipyroptotic and anti-migration effects of H3 relaxin by transmission electron microscopy, wound-healing assay, transwell assay, flow cytometry, cytokine assays and western-blot analysis. After H3 relaxin treatment, changes of the ultrastructure and expression of NLRP3 inflammasome related proteins in the retinas of rats were compared with those in the diabetic group. In vitro, H3 relaxin played a beneficial role that decreased cell inflammation, apoptosis, pyroptosis and migration stimulated by advanced glycation end products (AGEs). Moreover, inhibition of P2X7R and NLRP3 inflammasome activation decreased NLRP3 inflammasome-mediated injury that similar to the effects of H3 relaxin. H3 relaxin suppressed the stimulation of apoptosis, pyroptosis and migration of HRMECs in response to AGEs mediated by P2X7R activation of the NLRP3 inflammasome. Conclusion: Our findings provide new insights into the mechanisms of the inhibitory effect of H3 relaxin on AGE-induced retinal injury, including migration, apoptosis and pyroptosis, mediated by P2X7R-dependent activation of the NLRP3 inflammasome in HRMECs.